2007
DOI: 10.1007/s10551-007-9367-7
|View full text |Cite
|
Sign up to set email alerts
|

Salesperson Perceptions of Ethical Behaviors: Their Influence on Job Satisfaction and Turnover Intentions

Abstract: salesperson ethics, ethics and business relationships, ethics and job satisfaction, ethics and turnover, ethics measures,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 21 publications
3
80
1
7
Order By: Relevance
“…Similarly, Adeyeye, et al (2015) in their study on the "effects of workplace ethics on employees and organizational productivity in Nigeria", concluded that ethical climate in the organization influences the way employees to do their work and the total level of output. Also, the finding that intention to stay does not significantly influence the relationship between ethical culture and employee productivity is in consonance with the findings of Pettijohn, Pettijohn and Taylor (2008) who in their study on "ethical behaviours: Their influence on job satisfaction and turnover intentions", submit that employee intentions relatively influence their ethical behaviour which in turn influence their outcomes such as satisfaction, and productivity. In a more recent study, Valentine, et al (2011) investigated the relationship between "corporate ethical values, group creativity, job satisfaction and turnover intention" and came up with a similar result.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, Adeyeye, et al (2015) in their study on the "effects of workplace ethics on employees and organizational productivity in Nigeria", concluded that ethical climate in the organization influences the way employees to do their work and the total level of output. Also, the finding that intention to stay does not significantly influence the relationship between ethical culture and employee productivity is in consonance with the findings of Pettijohn, Pettijohn and Taylor (2008) who in their study on "ethical behaviours: Their influence on job satisfaction and turnover intentions", submit that employee intentions relatively influence their ethical behaviour which in turn influence their outcomes such as satisfaction, and productivity. In a more recent study, Valentine, et al (2011) investigated the relationship between "corporate ethical values, group creativity, job satisfaction and turnover intention" and came up with a similar result.…”
Section: Discussionsupporting
confidence: 83%
“…There are scanty empirical studies examining the correlation between these two variables (e.g., Patterson, War & West, 2004;Pattison & Edgar, 2011). Patterson, War and West (2004) examine the influence of company climate on its productivity using 42 production firms and found a significant relationship between the two variables.…”
Section: Ethical Culture and Employee Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also provided empirical support for the notion that a higher level of organizational ethics is associated positively with different individual outcomes, such as better job satisfaction (Jaramillo, Mulki, & Solomon, 2006;Pettijohn, Pettijohn, & Taylor, 2008;Valentine et al, 2011) and higher organizational commitment (e.g., Huhtala, Feldt, Hyvönen, & Mauno, 2013;Sharma, Borna, & Stearns, 2009;Treviño et al, 1998;Valentine, Godkin, & Lucero, 2002), which can reduce employees' turnover intentions (e.g., Jaramillo et al, 2006;Pettijohn et al, 2008;Valentine et al, 2011). Huhtala et al (2011) showed that ethical culture was associated with less ethical strain, less emotional exhaustion (the core dimension of burnout), and higher work engagement at the individual level.…”
Section: Ethical Culture As a Context For Well-beingmentioning
confidence: 99%
“…Employees who perceived they worked for an organization with an ethical climate were less likely to have turnover intentions (DeConinck, 2011;Jaramillo, Mulki, & Solomon, 2006;Mulki, Jaramillo, & Locander, 2006;Pettijohn, Pettijohn, & Taylor, 2008). Other potential benefits for organizations perceived as ethical included having to devote fewer resources to advertising and publicity to ameliorate negative press, providing a foundation for customer trust, and supporting positive ethical behavior by employees (Burton & Welty Peachey, 2014;Pettijohn et al, 2008).…”
Section: Ethical Work Climatementioning
confidence: 99%